2018
DOI: 10.7554/elife.32100
|View full text |Cite
|
Sign up to set email alerts
|

Perception of social interaction compresses subjective duration in an oxytocin-dependent manner

Abstract: Communication through body gestures permeates our daily life. Efficient perception of the message therein reflects one’s social cognitive competency. Here we report that such competency is manifested temporally as shortened subjective duration of social interactions: motion sequences showing agents acting communicatively are perceived to be significantly shorter in duration as compared with those acting noncommunicatively. The strength of this effect is negatively correlated with one’s autistic-like tendency. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 81 publications
(103 reference statements)
3
33
2
Order By: Relevance
“…Finally, our study adds onto a growing body of research investigating ensemble processes in social perception. This research found that two individuals are represented as a single unit when they are either facing (Papeo et al, 2017; Vestner et al, 2019) or interacting (Ding et al, 2017; Liu et al, 2018), and that this changes both how these stimuli are perceived (Liu et al, 2018; Papeo et al, 2017; Vestner et al, 2019) and remembered (Ding et al, 2017; Vestner et al, 2019). By showing that, despite identical input, the brain entrains more strongly to people moving together than to people moving independently, the current results reveal a potential neural mechanism of how ensemble processes shape social perception and evaluation.…”
Section: Discussionmentioning
confidence: 93%
“…Finally, our study adds onto a growing body of research investigating ensemble processes in social perception. This research found that two individuals are represented as a single unit when they are either facing (Papeo et al, 2017; Vestner et al, 2019) or interacting (Ding et al, 2017; Liu et al, 2018), and that this changes both how these stimuli are perceived (Liu et al, 2018; Papeo et al, 2017; Vestner et al, 2019) and remembered (Ding et al, 2017; Vestner et al, 2019). By showing that, despite identical input, the brain entrains more strongly to people moving together than to people moving independently, the current results reveal a potential neural mechanism of how ensemble processes shape social perception and evaluation.…”
Section: Discussionmentioning
confidence: 93%
“…In human embryonic kidney cells, OTR internalization was unaffected by inhibitors of protein kinase C (PKC) or CaMK-II but was significantly reduced after transfection with dominant-negative mutant cDNAs of GPCR kinase (GRK)2, β-arrestin 2, dynamin, and Eps15 (a component of clathrin-coated pits) (Patel and Radeos, 2018); GRK-evoked OTR phosphorylation was a prerequisite for β-arrestin-mediated internalization and OTR desensitization (Wang C. et al, 2018). In uterus, knockdown of GRK6 largely prevented OT-induced OTR desensitization; in contrast, selective depletion of GRKs 2, 3, or 5 was without effect (Denson et al, 2018; Liu et al, 2018). This signaling feature highlights a potentially beneficial effect of using intermittent OT application pattern in treating CVDs, the power of which has been well-discussed about studies on the milk-letdown reflex (Hatton and Wang, 2008; Hou et al, 2016).…”
Section: Signaling Pathways Mediating the Cardiovascular Protective Ementioning
confidence: 93%
“…Data analysis Previous studies asking observers to make an alternative choice in a task had applied the Boltzmann sigmoid function to fit the data (Liu, Yuan, Chen, Jiang, & Zhou, 2018;Wang & Jiang, 2012). In the present study, we made conducted a similar analysis to those in previous studies and first calculated the proportions of cabinet-with-sound sequences that were judged as being farther away than the singlecabinet sequence.…”
Section: Methodsmentioning
confidence: 99%